Prevalence, factors and early outcomes of frailty among hospitalized older patients with valvular heart disease: A prospective observational cohort study - Zhiyun Shen; Yuan Zhang; Daxin Zhou; Jiaying Lv; Chenxu Huang; Yihong Chen; Yuxia Zhang; Ying Lin (Wiley, 2024)
Abstract Aim The aim was to investigate the prevalence of, and factors related to frailty, together with early clinical outcomes, in hospitalized older patients with valvular heart disease (VHD) in China. Design A prospective observational cohort study was conducted. Methods A validated prospective survey was conducted to assess the prevalence of frailty, factors associated with it, and early clinical outcomes in hospitalized older patients with VHD, utilizing Fried's criterion. A total of 207 consecutive participants aged 65 years and older who underwent cardiac surgery were included in the study, spanning from September 2021 to December 2021. Results Frailty was detected in 78 patients (37.7%). Patients with multimorbidity, a New York Heart Association (NYHA) class of III/IV, or masticatory dysfunction had a greater incidence of frailty (p < 0.05). Patients with a normal albumin level and a higher frequency of exercise had a lower incidence of frailty (p < 0.05). Patients with frailty had longer hospital and intensive care unit stays and greater hospitalization costs than did those without frailty (p < 0.05). The 30‐day adverse event rate of the frail group was also greater (11.5% vs. 3.1%). Therefore, early screening for conditions such as multimorbidity, cardiac dysfunction, and hypoalbuminemia is urgently needed to effectively address frailty, as it has been linked to unfavourable early outcomes. Moreover, promoting exercise and improving masticatory function and nutrition are crucial for preventing and managing frailty in older patients with VHD.